A nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material and its preparation method and application, aluminum-air battery
By co-doping carbon fiber-loaded CoP composite material as the air cathode catalyst for aluminum air batteries, the existing precious metal catalysts have been solved, high conductivity and excellent oxygen reduction catalytic performance have been achieved, and the battery has been improved. stability and efficiency.
Patent Information
- Application Number
- CN202210123252.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-02-10
AI Technical Summary
The precious metal catalysts used in existing aluminum air batteries have low reserves, high costs and short service life, which limit their commercial development.
The nitrogen-phosphorus co-doped carbon fiber-supported CoP composite material was used as the air cathode catalyst to prepare the material by electrospinning and pyrolysis processes, and the CoP particles were coated with ZIF-8 derivative spherical carbon to improve the conductivity and catalytic activity of the material.
The high conductivity and excellent oxygen reduction catalytic performance of nitrogen and phosphorus co-doped carbon fiber-supported CoP composite material are achieved, which is comparable to the commercial 20 wt.% Pt/C catalyst, and has good stability and efficient electrochemistry. performance.
Smart Images

Figure CN114497590B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, a preparation method and application thereof, and an aluminum-air battery. Background Art
[0002] Aluminum-air battery is an energy storage device with high-purity aluminum Al (containing 99.99% aluminum) as the negative electrode, oxygen as the positive electrode, and potassium hydroxide (KOH) or sodium hydroxide (NaOH) aqueous solution as the electrolyte; the reaction mechanism is: aluminum absorbs oxygen from the air, and a chemical reaction occurs when the battery is discharged, and aluminum and oxygen react to convert into aluminum oxide. Aluminum-air batteries have the characteristics of low cost, theoretical energy density (2.98Ah / g) comparable to lithium (3.86Ah / g), low environmental pollution and recyclability. The catalytic activity of the air cathode catalyst is an important factor that directly affects the performance of aluminum-air batteries. At present, the most commonly used air cathode catalysts that are recognized to have better performance are precious metal catalysts, including metal platinum, palladium, gold or silver, but their low reserves, high costs and short service life limit their commercial development.
[0003] Transition metal-based catalysts have attracted great attention in the research field due to their high activity and stability. Among them, transition metal phosphide (TMP) materials have become a highly efficient catalytic material in recent years due to their unique catalytic and electronic properties. The electrocatalytic activity of transition metal phosphides is also highly dependent on factors such as the morphology and size of their nanostructures. Therefore, improving the catalytic activity of materials by controlling and adjusting the electronic structure and nanostructure of the materials has always been a research focus. Although a large amount of research on transition metal phosphides has been carried out, the conductivity of transition metal phosphides as catalysts is not ideal. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material having excellent electrical conductivity.
[0005] In order to achieve the purpose of the above invention, the present invention provides the following technical solutions:
[0006] The invention provides a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, comprising nitrogen-phosphorus co-doped carbon fiber, nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon and CoP particles, wherein the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon coats the CoP particles, and the nitrogen-phosphorus co-doped carbon fiber is loaded on the surface of the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon.
[0007] The present invention also provides a method for preparing the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material described in the above technical solution, comprising the following steps:
[0008] Providing ZIF-8 organic solution and polyacrylonitrile organic solution;
[0009] The ZIF-8 organic solution, cobalt phosphate and polyacrylonitrile organic solution are mixed to obtain a spinning precursor solution;
[0010] Electrospinning the spinning precursor solution to obtain a polyacrylonitrile nanofiber-loaded ZIF-8 film;
[0011] pre-oxidizing the polyacrylonitrile nanofiber-loaded ZIF-8 film to obtain a pre-oxidation product;
[0012] The pre-oxidation product is pyrolyzed in a N2 protective atmosphere to obtain the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material.
[0013] Preferably, the mass ratio of ZIF-8 to cobalt phosphate in the spinning precursor solution is (1.9-2.1): (0.8-1.2);
[0014] The mass ratio of ZIF-8 to polyacrylonitrile in the spinning precursor solution is (1.9-2.1): (1-1.3).
[0015] Preferably, the particle size of ZIF-8 particles in the ZIF-8 organic solution is ≤1 μm.
[0016] Preferably, the electrospinning conditions include: voltage of 18-20 kV, distance between the needle and the receiving plate of 15-20 cm, propulsion speed of 10-15 μL / min, temperature of 25-30° C., and humidity of 20%-40%.
[0017] Preferably, the pre-oxidation is carried out in an air atmosphere, the pre-oxidation time is 2 to 3 hours, and the insulation temperature is 230 to 240°C.
[0018] Preferably, the pyrolysis temperature is 1100-1120° C., and the insulation time is 2-2.5 h.
[0019] Preferably, the heating rate to the pyrolysis temperature is 2-5°C / min.
[0020] The present invention also provides the use of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material described in the above technical solution or the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material obtained by the preparation method described in the above technical solution as an air cathode catalyst in an air battery.
[0021] The present invention also provides an aluminum-air battery, comprising an aluminum-air battery cathode, an aluminum anode and an electrolyte, wherein the aluminum-air battery cathode material comprises a cathode active material and a catalyst, and the catalyst is the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material described in the above technical scheme or the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material obtained by the preparation method described in the above technical scheme.
[0022] The present invention provides a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, including nitrogen-phosphorus co-doped carbon fiber, nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon and CoP particles, wherein the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon coated CoP particles, and the nitrogen-phosphorus co-doped carbon fiber is loaded on the surface of the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon. In the present invention, ZIF-8 is formed by the coordination of zinc ions through 2-methylimidazole. The N atoms on 2-methylimidazole have Lewis basicity, and the pore structure helps to adsorb acidic carbon dioxide, has a good barrier effect on carbon dioxide, and can pass oxygen at the same time. Nitrogen-phosphorus co-doped modified ZIF-8 derived spherical carbon and carbon fiber form a carbon-based framework, which is beneficial to improving the oxygen reduction reaction activity of the catalyst. The structure of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material provided by the present invention is beneficial to providing the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material with good electrical conductivity, which is beneficial to the conduction of electrons in catalysis and promotes the smooth progress of the cathode catalytic reaction of the air battery.
[0023] The test results of the embodiments show that the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material provided by the present invention has excellent conductivity and exhibits good electrochemical performance when applied to the cathode of an aluminum-air battery.
[0024] The present invention also provides a preparation method of a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, comprising the following steps: mixing a ZIF-8 organic solution, cobalt phosphate and a polyacrylonitrile organic solution to obtain a spinning precursor solution; electrostatically spinning the spinning precursor solution to obtain a polyacrylonitrile nanofiber loaded ZIF-8 film; pre-oxidizing the polyacrylonitrile nanofiber loaded ZIF-8 film to obtain a pre-oxidation product; and pyrolyzing the pre-oxidation product in a N2 protective atmosphere to obtain the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material. In the present invention, ZIF-8 particles have an atomic-level confined dispersion effect on the Co element and are combined with electrostatic spinning. PAN in the spinning precursor solution is stretched into PAN nanofibers in a high-voltage electric field, and ZIF-8 particles are dispersed in the PAN system. During the spinning process, the particles are wrapped and connected in series by the nanofibers. In the final pyrolysis step, a carbon ball structure of carbon fibers connected in series is formed, and carbonization and phosphating occur during the pyrolysis process. The cobalt phosphate used in the present invention is relatively safe and effective. The carbon fiber material formed after carbonization and phosphating has high conductivity. The carbon balls derived from ZIF-8 particles wrap the CoP particles, which can promote the ORR reaction to react in a 4-electron path, improve the battery efficiency, have good oxygen reduction catalytic performance, and the catalytic activity is comparable to that of a commercial 20wt.% Pt / C catalyst. It can be used as a cathode catalyst for aluminum-air batteries and assembled into aluminum-air batteries to exhibit excellent discharge performance. After the obtained polyacrylonitrile nanofiber-loaded ZIF-8 film is pre-oxidized, the ZIF-8 in the polyacrylonitrile nanofiber-loaded ZIF-8 film can disperse Co atoms at the atomic level, and in the pyrolysis step, it can also play a confining role, hindering the high-temperature migration and agglomeration of Co atoms, effectively limiting the CoP particle size, and improving the oxygen reduction catalytic activity of the material. In the pyrolysis process of the preparation method provided by the present invention, carbonization and phosphating are carried out simultaneously, which is different from the complex high-temperature process of carbonization followed by phosphating in the prior art. The present invention avoids the further growth of CoP particles and the reduction of reaction activity. In addition, the preparation method provided by the present invention is simple in process and easy to industrially transform to realize industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A flow chart of the preparation method of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material provided by the present invention;
[0026] Figure 2 is the XRD pattern of ZIF-8 nanoparticles. DETAILED DESCRIPTION
[0027] The invention provides a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, comprising nitrogen-phosphorus co-doped carbon fiber, nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon and CoP particles, wherein the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon coats the CoP particles, and the nitrogen-phosphorus co-doped carbon fiber is loaded on the surface of the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon.
[0028] The present invention also provides a method for preparing the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material described in the above technical solution, comprising the following steps:
[0029] Providing ZIF-8 organic solution and polyacrylonitrile organic solution;
[0030] The ZIF-8 organic solution, cobalt phosphate and polyacrylonitrile organic solution are mixed to obtain a spinning precursor solution;
[0031] Electrospinning the spinning precursor solution to obtain a polyacrylonitrile nanofiber-loaded ZIF-8 film;
[0032] pre-oxidizing the polyacrylonitrile nanofiber-loaded ZIF-8 film to obtain a pre-oxidation product;
[0033] The pre-oxidation product is pyrolyzed in a N2 protective atmosphere to obtain the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material.
[0034] In the present invention, unless otherwise specified, each component in the technical solution is a commercially available product well known to those skilled in the art.
[0035] Figure 1 The preparation method of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material provided by the present invention is shown below in combination with Figure 1 The preparation method of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material provided by the present invention is described in detail.
[0036] The invention provides a ZIF-8 organic solution and a polyacrylonitrile organic solution.
[0037] The present invention preferably mixes ZIF-8 particles with an organic solvent to obtain a ZIF-8 organic solution.
[0038] In the present invention, the particle size of the ZIF-8 particles is preferably ≤1 μm. The present invention does not specifically limit the source of the ZIF-8 particles, and the source familiar to those skilled in the art can be used, specifically, such as purchase or preparation. In a specific embodiment of the present invention, the preparation method of the ZIF-8 particles is preferably: dissolving 2.5 mmol of Zn(NO3)2·6H2O in 50 mL of methanol to obtain a zinc nitrate solution; dissolving 20 mmol of 2-methylimidazole in 50 mL of methanol to obtain 2-methylimidazole; mixing the zinc nitrate solution with 2-methylimidazole, stirring at room temperature for 1 hour, centrifuging and separating the precipitate, washing with methanol, and then heating to 60°C in a vacuum drying oven to dry to obtain the ZIF-8 particles.
[0039] In the present invention, the ZIF-8 particles are preferably washed with methanol and DMF in sequence before use; the present invention has no special limitation on the specific operation of the washing, as long as the impurities attached to the ZIF-8 particles and the unreacted raw materials can be cleaned and removed.
[0040] In the present invention, the organic solvent is preferably N,N-dimethylformamide (DMF). The present invention has no special limitation on the amount of DMF, which is based on the amount that can ensure the dissolution of ZIF-8 particles. In a specific embodiment of the present invention, the ratio of the mass of ZIF-8 particles to the volume of DMF is preferably 1 g: 1 mL.
[0041] In the present invention, the ZIF-8 particles and the organic solvent are preferably mixed by stirring; the stirring temperature is preferably 60° C., and the stirring time is preferably 6 hours; the present invention has no particular limitation on the stirring speed, as long as complete mixing is possible.
[0042] In the present invention, polyacrylonitrile (PAN) is preferably mixed with an organic solvent to obtain a polyacrylonitrile solution.
[0043] In the present invention, the M of the polyacrylonitrile w Preferably it is 130,000 to 150,000.
[0044] In the present invention, the organic solvent is preferably N,N-dimethylformamide (DMF). The present invention has no special limitation on the amount of DMF used, as long as it can ensure the dissolution of polyacrylonitrile. In a specific embodiment of the present invention, the ratio of the mass of polyacrylonitrile to the volume of DMF is preferably 0.5g:4mL.
[0045] In the present invention, the mixing of polyacrylonitrile (PAN) and the organic solvent is preferably performed by stirring; the stirring temperature is preferably 60° C.; the stirring time is preferably 6 hours; the present invention has no particular limitation on the stirring speed, as long as complete mixing is possible.
[0046] After obtaining the ZIF-8 organic solution and the polyacrylonitrile organic solution, the present invention mixes the ZIF-8 organic solution with the cobalt phosphate and polyacrylonitrile organic solutions to obtain a spinning precursor solution.
[0047] In the present invention, the cobalt phosphate is preferably 98% Co3(PO4)2·8H2O.
[0048] In the present invention, the mass ratio of ZIF-8 to cobalt phosphate in the spinning precursor solution is preferably (1.9-2.1): (0.8-1.2), more preferably (1.95-2.05): (0.85-1.15). In the present invention, the mass ratio of ZIF-8 to polyacrylonitrile in the spinning precursor solution is preferably (1.9-2.1): (1-1.3), more preferably (1.95-2.05): (1.05-1.25).
[0049] The present invention has no special limitation on the mixing method of the ZIF-8 organic solution, cobalt phosphate and polyacrylonitrile organic solution, as long as a uniform spinning precursor solution can be obtained.
[0050] After obtaining the spinning precursor solution, the present invention performs electrostatic spinning on the spinning precursor solution to obtain a polyacrylonitrile nanofiber loaded ZIF-8 film.
[0051] In the present invention, the conditions for electrospinning include: the voltage is preferably 18-20 kV, more preferably 18.5-19.5 kV; the distance between the needle and the receiving plate is preferably 15-20 cm, more preferably 15-18 cm; the propulsion speed is preferably 10-15 μL / min, more preferably 10-13 μL / min; the temperature is preferably 25-30°C, more preferably 25-28°C; the humidity is preferably 20%-40%, more preferably 30-40%.
[0052] In the present invention, the receiving plate is preferably an aluminum foil receiving plate.
[0053] After the electrospinning is completed, the present invention preferably peels off the electrospinning product obtained from the aluminum foil receiving plate to obtain the polyacrylonitrile nanofiber-loaded ZIF-8 film.
[0054] After obtaining the polyacrylonitrile nanofiber loaded ZIF-8 film, the present invention pre-oxidizes the polyacrylonitrile nanofiber loaded ZIF-8 film to obtain a pre-oxidation product.
[0055] In the present invention, the pre-oxidation is preferably carried out in an air atmosphere. In the present invention, the pre-oxidation temperature is preferably 230-240°C, more preferably 232-238°C; the holding time is preferably 2-3h, more preferably 2.2-2.8h. In the present invention, during the pre-oxidation process, the polyacrylonitrile nanofiber-loaded ZIF-8 film undergoes cyclization, dehydrogenation, oxidation and cracking, and a polycondensation reaction occurs during pyrolysis to form carbon fibers.
[0056] After obtaining the pre-oxidation product, the present invention pyrolyzes the pre-oxidation product in a N2 protective atmosphere to obtain the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material.
[0057] In the present invention, the pyrolysis temperature is preferably 1100-1120°C, more preferably 1105-1115°C; the holding time is preferably 2-2.5h, more preferably 2.1-2.4h. In the present invention, the pyrolysis equipment is preferably a tubular furnace.
[0058] In the present invention, the pyrolysis process includes two processes: carbonization and phosphating. Specifically, the ZIF-8 particles and the COO functional groups in the spinning precursor undergo a carbonization reaction to form a carbon matrix and reduce the zinc therein to metallic zinc, and the cobalt in the cobalt phosphate is reduced to metallic cobalt. The non-carbon atoms (such as O, N, H, etc.) in the spinning precursor escape at high temperature, and the P decomposed from the phosphate in the cobalt phosphate in the precursor at high temperature will enter the carbon matrix to form phosphorus-modified carbon and react with metallic zinc and cobalt. Under the pyrolysis temperature conditions, ZnP escapes as steam (ZnP boiling point 1100°C, CoP melting point 1380°C), and finally CoP is obtained. In the present invention, the heating rate to the temperature of the pyrolysis is preferably 2-5°C / min, more preferably 3-4°C / min.
[0059] After the pyrolysis is completed, the present invention preferably cools the obtained pyrolysis product naturally to room temperature to obtain the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material.
[0060] The present invention also provides the use of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material described in the above technical solution or the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material obtained by the preparation method described in the above technical solution as an air cathode catalyst in an air battery.
[0061] In the present invention, the air battery is preferably an aluminum-air battery.
[0062] The present invention has no special limitation on the application, and the application of air cathode catalysts in air batteries well known to those skilled in the art can be used.
[0063] The present invention also provides an aluminum-air battery, comprising an aluminum-air battery cathode, an aluminum anode and an electrolyte, wherein the aluminum-air battery cathode material comprises a cathode active material and a catalyst, and the catalyst is the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material described in the above technical scheme or the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material obtained by the preparation method described in the above technical scheme.
[0064] In the present invention, the cathode material of the aluminum-air battery comprises the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material described in the above technical solution, which will not be described in detail here.
[0065] In the present invention, the cathode material of the aluminum-air battery preferably includes a catalyst layer, a current collecting layer and a gas diffusion layer (GDL) stacked in sequence, and the catalyst layer contains the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material.
[0066] In the present invention, the current collecting layer is preferably nickel foam.
[0067] In the present invention, the catalytic layer is preferably prepared by a method comprising the following steps:
[0068] After mixing the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, a conductive agent, a binder and an organic solvent, evaporating the organic solvent to obtain a viscous concentrated slurry;
[0069] The viscous concentrated slurry is coated on one side of the nickel foam to obtain the catalytic layer.
[0070] In the present invention, the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, a conductive agent, a binder and an organic solvent are mixed, and then the organic solvent is evaporated to obtain a viscous concentrated slurry.
[0071] In a specific embodiment of the present invention, the order of adding the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, conductive agent, binder and organic solvent is preferably: grinding the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material and conductive agent evenly, and then adding them to the organic solvent together with the binder.
[0072] In an embodiment of the present invention, the conductive agent preferably includes activated carbon and Ketjen black. In an embodiment of the present invention, the binder preferably includes polytetrafluoroethylene. In the present invention, the polytetrafluoroethylene is preferably used in the form of a polytetrafluoroethylene solution. In an embodiment of the present invention, the organic solvent preferably includes ethanol.
[0073] In an embodiment of the present invention, the mass ratio of the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material to the conductive agent is preferably (6-8): (8-10), more preferably (6.5-7.5): (8.5-9.5), and most preferably 7: 9. In an embodiment of the present invention, the mass ratio of the activated carbon to Ketjen black is preferably (6-8): (1-3), more preferably (6.5-7.5): (1.5-2.5), and most preferably 7: 2.
[0074] In an embodiment of the present invention, the ratio of the mass of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material to the volume of the polytetrafluoroethylene solution is preferably (60-80) mg: (580-620) μL, more preferably (65-75) mg: (590-610) μL, and most preferably 70 mg: 600 μL. In an embodiment of the present invention, the mass percentage concentration of polytetrafluoroethylene in the polytetrafluoroethylene solution is preferably 4-6%, more preferably 4.5-5.5%, and most preferably 5%.
[0075] In the present invention, the volume ratio of the polytetrafluoroethylene solution to ethanol is preferably (0.8-1.2):(18-22), more preferably (0.9-1.1):(19-21), and most preferably 1:20.
[0076] After obtaining the viscous concentrated slurry, the present invention coats the viscous concentrated slurry on one side of the nickel foam to obtain the catalytic layer.
[0077] The present invention has no particular limitation on the coating, and any coating known to those skilled in the art may be used.
[0078] In the present invention, the gas diffusion layer is preferably prepared by a method comprising the following steps: mixing polytetrafluoroethylene solution, Ketjen black, activated carbon and ethanol, and coating the mixture on the other side of the nickel foam in the above-mentioned catalyst layer preparation method.
[0079] In an embodiment of the present invention, the dosage ratio of the polytetrafluoroethylene solution, Ketjen black, activated carbon and ethanol is preferably (68-72) mg: (18-22) mg: (8-12) mg: (8-12) mL, more preferably (69-71) mg: (19-21) mg: (9-11) mg: (9-11) mL, and most preferably 70 mg: 20 mg: 10 mg: 10 mL; the mass percentage concentration of the polytetrafluoroethylene solution is preferably 58-62%, more preferably 59-61%, and most preferably 60%.
[0080] The present invention preferably utilizes a hot press to apply pressure to the catalyst layer, the current collecting layer and the gas diffusion layer, and then sequentially performs drying and sintering to obtain the aluminum-air battery cathode material.
[0081] In the present invention, the drying temperature is preferably 145-155°C, more preferably 148-153°C, and most preferably 150°C.
[0082] In the present invention, the sintering temperature is preferably 330-370° C., more preferably 340-360° C., and most preferably 350° C.; the sintering time is preferably 0.8-1.2 h, more preferably 0.9-1.1 h, and most preferably 1 h.
[0083] In the present invention, the aluminum-air battery further includes an aluminum anode and an electrolyte.
[0084] In the present invention, the aluminum anode in the aluminum-air battery is preferably high-purity aluminum, more preferably 4NAl.
[0085] In the present invention, the electrolyte of the aluminum-air battery is preferably a sodium hydroxide aqueous solution. In the present invention, the concentration of the sodium hydroxide aqueous solution is preferably 3 to 5 mol / L, more preferably 3.5 to 4.5 mol / L, and most preferably 4 mol / L.
[0086] In order to further illustrate the present invention, a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, its preparation method and application, and aluminum-air battery provided by the present invention are described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0087] Example 1
[0088] 2.5 mmol of Zn(NO3)2·6H2O was dissolved in 50 mL of methanol, and 20 mmol of 2-methylimidazole was dissolved in 50 mL of methanol. The two were then mixed, stirred at room temperature for 1 h, centrifuged to separate the precipitate, washed with methanol several times, and then heated to 60 °C in a vacuum drying oven and dried overnight to obtain ZIF-8 particles with a particle size of ≤1 μm.
[0089] 1.9 g of the prepared ZIF-8 particles were washed with methanol and DMF in turn, and then 1 mL of DMF was added and stirred evenly to obtain a ZIF-8 organic solution; 0.8 g of 98% reagent pure cobalt phosphate (Co3(PO4)2·8H2O) was weighed; 0.5 g of PAN (M w=130000~150000) was dissolved in 4mL of DMF, and the mass ratio of ZIF-8 particles to cobalt phosphate and PAN was controlled to be 1.9:0.8:1, and stirred at 60℃ for 6h, and then the above three solutions were mixed and stirred evenly to form a spinning precursor solution. The precursor solution was sucked into the needle tube for electrospinning. The specific parameters of electrospinning were: voltage of 18kV, distance between the needle and the receiving plate of 15cm, propulsion speed of 10μL / min, temperature of 25℃, and humidity of 20%, and a purple polyacrylonitrile nanofiber loaded ZIF-8 film was obtained;
[0090] After the electrospinning is completed, the polyacrylonitrile nanofiber-loaded ZIF-8 film is peeled off the aluminum foil receiving plate. First, the electrospinning film is pre-oxidized at 230°C for 2 hours under air atmosphere; after pre-oxidation, it is placed in a tubular furnace and N2 gas is introduced, and the temperature is raised to 1100°C at a rate of 2°C / min and kept warm for 2 hours. After naturally cooling to room temperature, a nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material (denoted as CoP@G / NP-PCNFs) is obtained.
[0091] Comparative Example 1
[0092] Prepare ZIF-8 particles according to the method of Example 1;
[0093] After the ZIF-8 nanoparticles were dried, they were directly mixed with cobalt phosphate (Co3(PO4)2·8H2O, where the mass ratio of ZIF-8 particles to cobalt phosphate was 2:0.8, and the resulting mixture was pyrolyzed at 1100°C for 2h to obtain a pyrolysis product (denoted as CoP / C).
[0094] test:
[0095] 1) X-ray diffraction test
[0096] The ZIF-8 obtained in Example 1 was subjected to an X-ray diffraction test, and the obtained XRD pattern is shown in Figure 2 .Depend on Figure 2 It can be seen that by comparing with the standard PDF card, the obtained purple powder is ZIF-8.
[0097] The nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material obtained in Example 1 was subjected to an X-ray diffraction test. The test results show that after heat treatment, an amorphous carbon-loaded matrix and CoP with good crystallinity (PDF#29-0497, Orthorhombic, ) particles. The diffraction peak corresponding to graphitized carbon is around 26°, which coincides with the diffraction peak of amorphous carbon, proving that the carbonaceous matrix contains graphitized carbon components. The graphitization of the carbon matrix also helps to improve the conductivity of the electrode, thereby greatly improving battery performance.
[0098] 2) X-ray photoelectron spectroscopy test
[0099] The nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material obtained in Example 1 was subjected to an X-ray photoelectron spectrum test to obtain the XPS full spectrum, C 1s orbital XPS spectrum, Co 2p orbital XPS spectrum, N 1s orbital XPS spectrum and P 2p orbital XPS spectrum of the prepared nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material. It can be seen from the test results that the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material mainly contains 5 main elements: C, N, O, Co and P. The modified elements on the carbon matrix include O, P and N. Because XPS detection focuses on the chemical state of the elements on the surface of the sample, these catalysts will inevitably be oxidized in the air, so the O element will inevitably appear. The test graph of the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material contains obvious Co metal peaks (779.1eV, 794eV) and CoP peaks (781.9eV, 798eV), as well as the accompanying satellite peaks (786.7eV, 803.2eV), indicating that CoP particles are formed in the catalyst carbon matrix. There are four states of N in the modified carbon matrix in the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material: pyridinic nitrogen (398.4eV), pyrrolic nitrogen (399.4eV), graphitic nitrogen (401eV) and N oxide (403.5eV), among which pyridinic nitrogen and graphitic nitrogen especially promote the oxygen reduction reaction, which helps to increase the reaction efficiency and improve the battery power. The oxide peak of P (132.6eV) and the peak of PC bond (133.4eV) correspond to the C1s orbital fitting peak data, proving the presence of P atom modification on the carbon matrix. The modification of P also has a certain effect on improving the activity of the catalyst in the catalytic reaction. The final material obtains excellent oxygen reduction catalytic performance, which is comparable to 20wt.% Pt / C.
[0100] 3) Scanning electron microscope test
[0101] The nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material prepared in Example 1 was subjected to a scanning electron microscope test. It can be seen from the test results that the ZIF-8 nanospheres were successfully loaded onto the spun fibers, and after carbonization / phosphating (800°C×2h), a long bundle of carbon fibers was connected in series to load a large number of carbon spheres in a beaded morphology, wherein the average diameter of the carbon fibers was 150nm, the diameter of the carbon spheres was 1μm, and there were many pores on the surfaces of the carbon fibers and carbon spheres. Carbon spheres loaded with carbon fibers effectively avoid the agglomeration of ZIF-8 during the pyrolysis process. The presence of carbon spheres increases the specific surface area of the material, which is beneficial to the transmission of oxygen, and the carbon fibers can efficiently transmit electrons, thereby achieving a good oxygen reduction catalytic effect.
[0102] 4) Transmission electron microscopy test
[0103] The nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material obtained in Example 1 was subjected to transmission electron microscopy test to obtain TEM images and high-power transmission electron microscopy images of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material. It can be seen from the test results that the diameter of the ZIF-8 nanoparticles after carbonization is 1 μm, which is similar to the results of the scanning image analysis; a large number of nanoparticles are evenly distributed in these carbonized particles, and combined with the XRD data analysis, it should be CoP, and its size is between a few nanometers and 100nm. The particle crystal plane is (101) and the interplanar spacing is 0.375nm. Since ZIF-8 itself has an atomic-level dispersion effect on metal elements, it has a strong confinement ability during high-temperature pyrolysis, which greatly limits the agglomeration and growth of Co, and finally retains a large number of nanoscale CoP particles; smaller nanoparticles have a larger specific surface area and a higher reaction activity, thereby improving the oxygen reduction catalytic effect of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material.
[0104] 5) Electrochemical test of oxygen reduction catalytic activity
[0105] Preparation of disk thin film electrode:
[0106] 10 mg of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material prepared in Example 1 and 10 mg of acetylene black were dispersed in 2 mL of anhydrous ethanol, and 20 uL of 5 wt.% Nafion solution was added. After ultrasonic dispersion for 30 min, 2 μL was added dropwise to a polished glassy carbon electrode (5 mm in diameter), and dried for 2 h to obtain a disk film electrode. The catalytic performance was tested using a rotating disk electrode test body system, using a three-electrode system (a glassy carbon electrode loaded with a catalytic layer as a working electrode, a Pt electrode as a counter electrode, and a Hg / HgO electrode (with a built-in solution of 0.1 mol / L KOH solution) as a reference electrode) in a 0.1 mol / L KOH electrolyte.
[0107] Cyclic voltammetry curves of 20wt.% Pt / C, CoP / C and the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material prepared in Example 1 in an O2-saturated 0.1M NaOH solution were tested at a scan rate of 30mV·S -1 The test results show that in the O2-saturated 1M KOH solution, an obvious redox peak was found, proving that a redox reaction occurred. The oxygen reduction peak potential that characterizes the oxygen reduction catalytic performance can be analyzed. The oxygen reduction peak potential of the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material was analyzed to be 0.828V vs RHE.
[0108] The linear polarization curves of 20wt.% Pt / C, CoP / C and the nitrogen-phosphorus co-doped carbon fiber-supported CoP composite material prepared in Example 1 were tested in 0.1M NaOH solution. The test results can be used to analyze the starting potential, half-wave potential, and limiting current density information that characterize the oxygen reduction catalytic performance. After analysis, the starting potential of the nitrogen-phosphorus co-doped carbon fiber-supported CoP composite material prepared in Example 1 is 0.908V vs RHE, the half-wave potential is 0.84Vvs RHE, and the limiting diffusion current density is 3.83mA·cm -2 .
[0109] At different speeds (400 rpm to 1600 rpm), with a scan rate of 5 mV·s -1 A series of LSV curves of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material obtained in Test Example 1. It can be seen from the test results that with the increase of the rotation speed, the starting potential at each rotation speed remains basically unchanged, while the limiting current density continues to increase. The current density value at different voltages can be extracted, and then the number of transferred electrons (n) can be calculated by the slope of the Koutecky-Levich (KL) formula, as follows:
[0110] 1 / j=1 / j k +1 / (Bω 1 / 2 )
[0111] j k =nFkC0
[0112] Where, j: measured current density, j k : kinetic current density, ω: angular velocity of rotation, k: electron transfer rate constant, B is the inverse of the Koutecky-Levich (KL) slope,
[0113] B = 0.62nFD02 / 3v-1 / 6C0,
[0114] Where n: number of electrons transferred in the ORR process; F: Faraday constant (96485 C·mol -1 ); D0: diffusion coefficient of oxygen in 0.1M NaOH (1.9×10 -5 cm 2 ·s -1 ); v: dynamic viscosity coefficient of electrolyte (0.01cm 2 ·s -1 ); C0: saturated concentration of O2 in 0.1M NaOH at 1atm O2 pressure (1.2×10 -3 mol cm -3). When the speed ω is measured in "rpm" (Revolutions Per Minute), the constant is "0.2"; when the speed is measured in "rad / s" (Radian Per Second), the constant is "0.62". For comparison, commercial 20wt.% Pt / C was measured under the same conditions, and the results were analyzed in parallel.
[0115] The number of transferred electrons calculated by the KL equation, specifically, at voltages of -0.05, 0.00, 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75 V vs RHE, the calculated number of transferred electrons, the data points collected at different voltages. According to the collected results, the average number of transferred electrons is 3.89, indicating that the electron transfer process of the nitrogen-phosphorus co-doped carbon fiber-supported CoP composite material in the catalytic oxygen reduction process obeys 4-electron transfer.
[0116] Application Example 1
[0117] The high and low temperature test of aluminum-air battery was carried out in a homemade battery model in the laboratory:
[0118] The air electrode consists of a catalyst layer, a current collecting layer (nickel foam) and a gas diffusion layer (GDL):
[0119] The preparation method of the catalytic layer is as follows: 70 mg of the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material prepared in Example 1, 70 mg of activated carbon and 20 mg of Ketjen black are evenly ground, the obtained mixture and 600 μL of polytetrafluoroethylene solution (5 wt.%) are added to 12 mL of ethanol, the obtained mixed solution is magnetically stirred evenly, and heated to volatilize the ethanol to obtain a viscous concentrated slurry; the obtained viscous concentrated slurry is coated on one side of the nickel foam;
[0120] The gas diffusion layer was prepared by adding 70 mg of polytetrafluoroethylene (60 wt.%), 20 mg of Ketjen black and 10 mg of activated carbon to 10 ml of ethanol, stirring with a magnetic stirrer to form a uniform slurry, and applying the resulting slurry to the other side of the nickel foam;
[0121] A hot press was used to apply pressure to the nickel foam coated with the catalytic layer and the gas diffusion layer slurry on both sides, and then it was dried at 150°C in a vacuum oven and finally kept at 350°C in a tubular furnace for 1 hour to obtain the aluminum air battery cathode.
[0122] The obtained aluminum-air battery cathode and high-purity aluminum (4N Al) anode were assembled into an aluminum-air battery mold, and a 4M NaOH solution was injected to obtain an aluminum-air battery.
[0123] The aluminum-air battery obtained in Example 1 was subjected to a dynamic discharge test (discharge for 30 minutes at each discharge current density), and the step constant current discharge curve was recorded; the step constant current discharge power density curve of the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite cathode and high-purity aluminum in 4M NaOH electrolyte was tested. From the test results, it can be seen that the aluminum-air battery assembled with the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite cathode is basically stable at each current density, and maintains a relatively stable discharge platform at different current densities. In 4M NaOH solution, when the discharge current density is low (1mA·cm -2 , 5mA·cm -2 、10mA·cm -2 , 20mA·cm -2 、35mA·cm -2 ), the discharge voltage is higher; but when the current density increases to a higher value (≥50mA·cm -2 ) when the discharge voltage drops rapidly, the voltage platform fluctuation increases, and the stability decreases. Its power density increases first and then decreases with the increase of current density, and the peak value appears at 80mA·cm -2 , is 72.8 mW·cm -2 .
[0124] The nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material and CoP / C catalyst prepared in Example 1 were compared with the commercial 20wt.% Pt / C catalytic performance, and the aluminum-air battery constant current discharge and step discharge performance were tested to obtain the relationship curve between the discharge voltage and current density of 20wt.% Pt / C, CoP / C and the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material prepared in Example 1 in the aluminum-air battery. From the test results, it can be seen that the 20wt.% Pt / C step discharge voltage is higher at low current density, and when the current density reaches 10mA / cm 2 When the above values are given, the cathode voltage prepared by the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material is higher, while the cathode prepared by the CoP / C catalytic reaction has the lowest voltage.
[0125] The discharge voltage and specific capacity curves of 20wt.% Pt / C and the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material prepared in Example 1 were tested in aluminum-air batteries. From the test results, it can be seen that the specific capacity of the anode of the aluminum-air battery with 20wt.% Pt / C as the cathode catalyst is only 2647.7mAh / g, while the cathode prepared with the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material prepared in Example 1 makes the anode capacity reach 2824.3mAh / g, proving that the oxygen reduction catalytic effect of the nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material provided by the present invention is comparable to that of the catalytic effect of the 20wt.% Pt / C catalyst, and has better stability.
[0126] Example 2
[0127] According to the method of Example 1, ZIF-8 particles with a particle size of ≤1 μm were obtained;
[0128] 2.1 g of the prepared ZIF-8 particles were washed with methanol and DMF in turn, and then 1 mL of DMF was added and stirred evenly to obtain a ZIF-8 organic solution; 1.2 g of reagent-grade cobalt phosphate with a mass percentage concentration of 98% was weighed; 1.3 g of PAN (M w =130000~150000) was dissolved in 4mL of DMF, the mass ratio of ZIF-8 particles to cobalt phosphate and PAN was controlled to be 1.1:1.2:1.3, and stirred at 60℃ for 6h, and then the above three solutions were mixed and stirred evenly to form a spinning precursor solution. The precursor solution was sucked into the needle tube for electrospinning. The specific parameters of electrospinning were: voltage of 20kV, distance between the needle and the receiving plate of 20cm, propulsion speed of 20μL / min, temperature of 30℃, humidity of 40%, and purple polyacrylonitrile nanofiber loaded ZIF-8 film was obtained;
[0129] After the electrospinning is completed, the polyacrylonitrile nanofiber-loaded ZIF-8 film is peeled off the aluminum foil receiving plate. First, the electrospinning film is pre-oxidized at 240°C for 3 hours under air atmosphere; after pre-oxidation, it is placed in a tubular furnace and N2 gas is introduced, and the temperature is increased to 1120°C at a rate of 2°C / min and kept warm for 2.5 hours. After naturally cooling to room temperature, a nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material is obtained.
[0130] Example 3
[0131] According to the method of Example 1, ZIF-8 particles with a particle size of ≤1 μm were obtained;
[0132] 2.0 g of the prepared ZIF-8 particles were washed with methanol and DMF in turn, and then 1 mL of DMF was added and stirred evenly to obtain a ZIF-8 organic solution; 1 g of reagent-grade cobalt phosphate with a mass percentage concentration of 98% was weighed; 1.15 g of PAN (M w =130000~150000) was dissolved in 4mL of DMF, the mass ratio of ZIF-8 particles to cobalt phosphate and PAN was controlled to be 2:1:1.15, and stirred at 60℃ for 6h, and then the above three solutions were mixed and stirred to form a spinning precursor solution. The precursor solution was sucked into the needle tube for electrospinning. The specific parameters of electrospinning were: voltage of 19kV, distance between the needle and the receiving plate of 17.5cm, propulsion speed of 12.5μL / min, temperature of 27.5℃, humidity of 30%, and purple polyacrylonitrile nanofiber loaded ZIF-8 film was obtained;
[0133] After the electrospinning is completed, the polyacrylonitrile nanofiber-loaded ZIF-8 film is peeled off the aluminum foil receiving plate. First, the electrospinning film is pre-oxidized at 235°C for 2.5 hours under air atmosphere; after pre-oxidation, it is placed in a tubular furnace and N2 gas is introduced, and the temperature is increased to 1110°C at a rate of 2°C / min and kept warm for 2.25 hours. After naturally cooling to room temperature, a nitrogen-phosphorus co-doped carbon fiber-loaded CoP composite material is obtained.
[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material, characterized in that: The following steps are involved: Providing a ZIF-8 organic solution and a polyacrylonitrile organic solution; mixing ZIF-8 particles with the organic solvent to obtain the ZIF-8 organic solution; Mixing ZIF-8 organic solution, cobalt phosphate and polyacrylonitrile organic solution to obtain a spinning precursor solution; the mass ratio of ZIF-8 to cobalt phosphate in the spinning precursor solution is (1.9-2.1): (0.8-1.2); the cobalt phosphate is Co3(PO4)2·8H2O with a mass percentage concentration of 98%; Electrospinning the spinning precursor solution to obtain a polyacrylonitrile nanofiber-loaded ZIF-8 film; pre-oxidizing the polyacrylonitrile nanofiber-loaded ZIF-8 film to obtain a pre-oxidation product; The pre-oxidation product is pyrolyzed in a N2 protective atmosphere to obtain the nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material; the pyrolysis temperature is 1100-1120° C., and the insulation time is 2-2.5 hours; The nitrogen-phosphorus co-doped carbon fiber loaded CoP composite material comprises nitrogen-phosphorus co-doped carbon fiber, nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon and CoP particles, the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon coated CoP particles, and the nitrogen-phosphorus co-doped carbon fiber is loaded on the surface of the nitrogen-phosphorus co-doped ZIF-8 derived spherical carbon; The preparation method of the ZIF-8 particles is as follows: dissolving 2.5 mmol of Zn(NO3)2·6H2O in 50 mL of methanol to obtain a zinc nitrate solution; dissolving 20 mmol of 2-methylimidazole in 50 mL of methanol to obtain 2-methylimidazole; mixing the zinc nitrate solution and 2-methylimidazole, stirring at room temperature for 1 hour, centrifuging and separating the precipitate, washing with methanol, and then heating to 60°C in a vacuum drying oven to dry, to obtain the ZIF-8 particles.
2. The preparation method according to claim 1, characterized in that: The mass ratio of ZIF-8 to polyacrylonitrile in the spinning precursor solution is (1.9-2.1): (1-1.3).
3. The preparation method according to claim 1, characterized in that: The particle size of the ZIF-8 particles in the ZIF-8 organic solution is ≤1 μm.
4. The preparation method according to claim 1, characterized in that: The electrostatic spinning conditions include: voltage of 18-20 kV, distance between the needle and the receiving plate of 15-20 cm, propulsion speed of 10-15 μL / min, temperature of 25-30° C., and humidity of 20%-40%.
5. The preparation method according to claim 1, characterized in that: The pre-oxidation is carried out in an air atmosphere, the pre-oxidation time is 2 to 3 hours, and the insulation temperature is 230 to 240°C.
6. The preparation method according to claim 1, characterized in that: The heating rate to the pyrolysis temperature is 2-5°C / min.
Citation Information
Patent Citations
N-and-P double-doped carbon fiber-loaded CoP composite catalytic material as well as preparation method and application thereof
CN112928287A